OR32-06 Opportunistic Assessment of Pituitary Gland with Routine MRI and PET/CT Can Guide in Earlier and Increased Identification of Hypophysitis in Patients Treated with Combination Checkpoint Inhibitors - Galligan, Anna (J Endocr Soc, 2020)
Background: Hypophysitis is one of the commonly reported adverse events related to immune checkpoint inhibitors (ICI), and the incidence is expected to rise with increased use of combined programmed cell death protein 1 (PD1) and cytotoxic T lymphocyte associated protein 4 (CTLA4) blockade. The clinical diagnosis can be delayed due to non-specific symptoms. At our centre, subjects undergo periodic imaging to assess tumour response to ICI. We reviewed whether neuroimaging studies can guide us in the diagnosis of hypophysitis and whether early changes can be detected before the onset of the clinical syndrome. Methods: We retrospectively reviewed the medical charts, biochemistry, structural brain imaging and whole-body positron emission tomography (PET) with specific reference to hypophysitis in 162 patients treated with combination ICI at a tertiary melanoma referral centre. Suspected cases were identified based on meeting one or more of the following criteria: 1) A documented diagnosis of hypophysitis or pituitary dysfunction found on chart review, 2) A relative change in pituitary size or appearance from baseline on neuroimaging studies, or 3) An increase in pituitary maximum standardized uptake value (SUVmax) greater than 25% from baseline on (18)F-FDG PET. Results: 58/162 patients (36%) met criteria for suspected hypophysitis. Only 4 patients were identified on routine screening of early morning cortisol. 14 patients presented with symptoms leading to biochemical work up. A further 40 patients were found to have suspicious imaging changes, 13 of which went on to receive a formal diagnosis of hypophysitis. Of the remaining 27 patients, 23 were receiving high dose glucocorticoids for concomitant immune related adverse events at the time of the abnormal imaging study.Conclusion: We report the highest incidence to date of suspected hypophysitis in cohort of patients treated with combination ICI. This study highlights the important role of structural and functional neuroimaging in the early recognition of hypophysitis. Imaging may also play a role when the clinical syndrome is masked by concurrent glucocorticoid use.